A Prognostic Nomogram for T3N0 Rectal Cancer After Total Mesorectal Excision to Help Select Patients for Adjuvant Therapy - Zhang, Chao; Zhao, Shutao; Wang, Xudong (Frontiers in Oncology, 2021)
Background The recurrence rate of T3N0 rectal cancer after total mesorectal excision (TME) is relatively low, meaning that not all patients need adjuvant therapy (AT) (radiotherapy, chemotherapy, or chemoradiotherapy). Methods Patients diagnosed with pT3N0M0 rectal cancer after TME were analyzed using the SEER database, of which 4367 did not receive AT and 2794 received AT. Propensity score matching was used to balance the two groups in terms of confounding factors. Cox proportional hazards regression analysis was used to screen independent prognostic factors, which were then used to establish a nomogram. The patients were then divided into three groups with X-tile software according to their risk scores. We enrolled 334 patients as external validation. Results The C-index of the model was 0.725 (95% confidence interval: 0.694–0.756). We divided the patients into three different risk layers based on the nomogram prediction scores, and found that AT did not improve the prognosis of low- and moderate-risk patients, while high-risk patients benefited from AT. External validation data also support the above conclusions. Conclusion This study developed a nomogram that effectively and comprehensively evaluates the prognosis of T3N0 rectal cancer patients after TME. After using the nomogram, we recommend AT for high-risk patients, but not for low- and moderate-risk patients.